Financial Ratio Analysis as a Tool for Measuring the Financial Performance of PT Ultrajaya Milk Industry & Trading Company Tbk for the 2020–2024 Period - Bayu Firmanda; Cahyo Pramono; Aulia Aulia (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk during the period 2020–2024 using a financial ratio approach that includes liquidity, activity, profitability, and solvency ratios. This study employs a descriptive quantitative method using secondary data obtained from the company’s audited and published annual financial statements. Data analysis is conducted by calculating and evaluating financial ratios, including liquidity ratios, activity ratios, profitability ratios, and solvency ratios. The results indicate that PT Ultrajaya demonstrates a very strong level of liquidity, stable operational efficiency, and consistent profitability throughout the observation period despite external pressures arising from global economic dynamics. In addition, the company’s solvency ratios remain at a low level, indicating minimal dependence on debt-based financing. This study is subject to limitations, as it focuses on a single company, a limited observation period, and does not quantitatively incorporate macroeconomic variables. The findings are expected to contribute to the fields of financial accounting and financial management and to serve as a reference for investors, creditors, and management in assessing the financial resilience and effectiveness of financial strategies in the food and beverage industry amid global economic uncertainty.